2022
DOI: 10.1017/iop.2022.28
|View full text |Cite
|
Sign up to set email alerts
|

Is cybervetting valuable?

Abstract: Cybervetting is the widespread practice of employers culling information from social media and/or other internet sources to screen and select job candidates. Research evaluating online screening is still in its infancy; that which exists often assumes that it offers value and utility to employers as long as they can avoid discrimination claims. Given the increasing prevalence of cybervetting, it is extremely important to probe its challenges and limitations. We seek to initiate a discussion about the negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 104 publications
2
13
0
1
Order By: Relevance
“…Cybervetting is a growing but controversial practice (Landers & Schmidt, 2016;Mönke & Schäpers, 2022;Roth et al, 2016;Wilcox et al, 2022). Given that social media risk exposing recruiters to job-unrelated applicant information (e.g., political affiliation; Zhang et al, 2020), the PAM (Roth et al, 2017(Roth et al, , 2020 serves as an important conceptual capstone to better understand similarityattraction effects in cybervetting.…”
Section: Discussionmentioning
confidence: 99%
“…Cybervetting is a growing but controversial practice (Landers & Schmidt, 2016;Mönke & Schäpers, 2022;Roth et al, 2016;Wilcox et al, 2022). Given that social media risk exposing recruiters to job-unrelated applicant information (e.g., political affiliation; Zhang et al, 2020), the PAM (Roth et al, 2017(Roth et al, , 2020 serves as an important conceptual capstone to better understand similarityattraction effects in cybervetting.…”
Section: Discussionmentioning
confidence: 99%
“…Extant research has shown that when application procedures are anonymous, discriminatory effects can be minimized (Åslund & Skans, 2012), likely because name-blind applications limit available stimuli that can activate biases. Anonymous applications also limit the evaluator's ability to engage in cybervetting, which can have additional discriminatory impacts (Wilcox et al, 2022). Name-blind application processes are, however, an imperfect solution (O’Connor, 2016) as application information other than names can signal demographic characteristics and bias the selection process (Foley & Williamson, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Among for‐profit employers, especially small ones, cybervetting is viewed as a virtual necessity for minimizing the risk of problem hires. However, the practice is often eschewed by large and/or public sector organizations, which likely face higher expectations for transparency and fairness in their hiring practices (Wilcox et al., 2022). dLMI use also shifts with organizations' specific hiring goals.…”
Section: Discussionmentioning
confidence: 99%